Vertically integrated medical education and the readiness for practice of graduates. Issue 1 (December 2015) - Wijnen-Meijer, Marjo; ten Cate, Olle; van der Schaaf, Marieke; Burgers, Chantalle; Borleffs, Jan; Harendza, Sigrid
Abstract Background Medical curricula become more and more vertically integrated (VI) to prepare graduates better for clinical practice. VI curricula show early clinical education, integration of biomedical sciences and focus on increasing clinical responsibility levels for trainees. Results of earlier questionnaire-based studies indicate that the type of the curriculum can affect the perceived preparedness for work as perceived by students or supervisors. The aim of the present study is to determine difference in actual performance of graduates from VI and non-VI curricula. Methods We developed and implemented an authentic performance assessment based on different facets of competence for medical near-graduates in the role of beginning residents on a very busy day. Fifty nine candidates participated: 30 VI (Utrecht, The Netherlands) and 29 non-VI (Hamburg, Germany). Two physicians, one nurse and five standardized patients independently assessed each candidate on different facets of competence. Afterwards, the physicians indicated how much supervision they estimated each candidate would require on nine so called "Entrustable Professional Activities (EPAs)" unrelated to the observed scenarios. Results Graduates from a VI curriculum received significantly higher scores by the physicians for the facet of competence "active professional development", with features like 'reflection' and 'asking for feedback'. In addition, VI graduates scored better on the EPA "solving a management problem", while the non-VI graduates got higher scores for the EPA "breaking bad news". Conclusions This study gives an impression of the actual performance of medical graduates from VI and non-VI curricula. Even though not many differences were found, VI graduates got higher scores for features of professional development, which is important for postgraduate training and continuing education.